Which Arrived First? A Simple Experiment Using Smartphone to Analyze Parabolic and Free Fall Motion Simultaneously - S. Siswanto; H. Hartono; B. Subali; P. Marwoto; R. S. Iswari (International Conference on Science, Education, and Technology, 2021)
This study aims to describe a simple experiment by using an affordable-price smartphone to analyze two objects that do parabolic motion and free fall at the same height, at the same time. Students often experience misconceptions in understanding the concepts of free fall and parabolic motion. Not only the difficulty of the material, but this is also caused by the problem of conducting real experiments analyzing both movements. It is because both movements usually occur in a relatively short time. To be able to capture movement in detail, a high-speed camera in capturing objects is needed even though it is relatively expensive, so it cannot be reached by most teachers and students. The equipments used in this experiment are two coins, a ruler, a cardboard, and a smartphone. Videos recorded through a smartphone are analyzed by using the VidAnalysis application. The results showed that a simple experiment was able to describe two objects that move freely and parabolic at the same height, at the same time. Based on data analysis, both objects fell on the ground simultaneously. Besides, this experiment was also able to measure the acceleration of Earth's gravity.